Revenue Growth, Profit Growth, and Stock Prices: Ownership Structure Moderation - Muhammad Irfai Sohilauw (ARBITRASE: Journal of Economics and Accounting, 2025)
This study examines the effect of revenue and profit growth on the stock prices of PT Bali Bintang Sejahtera, Tbk, using financial report data from Bali United from January 2017 to December 2023 with E-Views 12 software. The analysis shows that revenue growth has a significant impact on profit growth (p=0.0127) and stock prices (p<0.0001). Meanwhile, profit growth has a significantly negative effect on stock prices (p=0.0013). The moderation of ownership structure on the relationship between profit growth and stock prices is not directly significant (p=0.4560), but the interaction between profit growth and ownership structure shows marginal significance (coefficient=0.461212, p=0.0931). Furthermore, the Sobel test indicates that profit growth partially mediates the impact of revenue growth on stock prices significantly (Sobel test statistic=2.0268, p=0.0427). This result is supported by the Aroian test (p=0.0468) and Goodman test (p=0.0369). These findings provide new insights into financial literature, particularly in the context of the football industry. Investors value revenue growth and club reputation more than short-term profits. This study reveals that the relationship between revenue growth, profit, and stock prices in the football industry exhibits unique dynamics compared to other sectors, highlighting the distinctive way football economics operates.